Perception of Engineering Undergraduates On the Needs of English Language in The Engineering Field - Mohamad Yusof, Nurdiyana; Yuslin, Ahmad Nabil Mubasyir; Awangku Ismail, Dayangku Aqilah (Selangor Humaniora Review, 2023)
The need for English language skills has increased across industries and workplaces due to globalisation. The engineering field, for instance, requires a certain level of English proficiency as English is commonly employed for various jobs. The current study is (1) to identify engineering students' perception of the English language's needs in the engineering industry and (2) to identify the most required English language skills by engineering undergraduates. This study's targeted participants were engineering majors at a private university in West Malaysia. To collect the data, a questionnaire was distributed, and 41 participants to the engineering students. Thus, the results of this study revealed that the use of the English language is significant in the engineering field and that English proficiency is essential for students to perform engineering-related tasks. Among the four main skills, listening and writing were rated the most needed skills among engineering students. This study suggests that English for specific purposes (i.e., engineering) should be included in the curriculum of engineering programmes.